Analýza spokojenosti zákazníků a návrhy na zlepšení její úrovně ve zvolené společnosti - Čapková, Zuzana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Diplomová práce se zabývá analýzou spokojenosti zákazníků a návrhy na zlepšení její úrovně ve společnosti IPI s.r.o.. Teoretická část je zaměřena na výklad pojmů, které souvisí s danou problematikou. Dále jsou analyzovány výsledky dotazníkového šetření, popsány příslušné analýzy společnosti a v závěru práce jsou stanovena doporučení a návrhy, které povedou ke zvýšení spokojenosti zákazníků ve vybrané společnosti.

The thesis deals with the analysis of customer satisfaction and suggestions for improvement of its level in IPI s.r.o.. The theoretical part is focused on the interpretation of concepts that are related to the given issues. Further the results of the questionnaire survey are analyzied, the relevant analyzes of the company are described and at the end of the thesis there are recommendations and suggestions that will lead to increasing the satisfaction of the customers in the selected company.
Customer Satisfaction Analysis and Suggested Measures for its Improvement in the Selected Company
Keywords: marketing; zákazník; spokojenost; analýza spokojenosti zákazníků; zvýšení spokojenosti zákazníků; dotazník; marketingový výzkum; marketing; customer; satisfaction; customer satisfaction analysis; increase of customer satisfaction; questionnaire; marketing research